A Tunable Dispersion‐Free Terahertz Metadevice with Pancharatnam–Berry‐Phase‐Enabled Modulation and Polarization Control. (30th September 2015) - Cong, Longqing; Xu, Ningning; Han, Jiaguang; Zhang, Weili; Singh, Ranjan
Abstract : It is extremely challenging to control the phase of light at will in free space. Here, Pancharatnam–Berry‐phase‐enabled, tunable phase control of free‐space light is experimentally demonstrated in an ultrathin flexible dispersion‐free metadevice. This metadevice enables the broadband conversion of linearly polarized light into any desired output polarization.